Contribuição de pósitrons e elétrons secundários para o espectro em rádio de explosões solares - Serra, Jordi Tuneu (2017)
Recent observations of solar flares at high-frequencies in radio and in the medium infrared have provided evidence of a new spectral component with fluxes increasing with frequency in the sub- to range. This new component occurs simultaneously but is separated from the well-known microwave spectral component that has a maximum at frequencies of order of tens of , resulting in a doublespectrum structure. Several mechanisms based on different emission processes have been proposed to interpret the new spectral component but its origin still remains unknown. The aim of this work is to study the mechanisms of production of secondary electrons and positrons in high-energy nuclear processes (∼ ) which occur in solar flares and its possible contribution to the spectral component via the emission of gyrosynchrotron/synchrotron radiation. We also discuss the possible contribution of low-energy secondary electrons (∼ 0.1 − 10 ) to the microwave spectrum of intense events. Using the package FLUKA, a Monte Carlo simulator for calculations of particle transport and interactions in matter, we obtain the energy distributions for secondary electrons and positrons generated by collisions between accelerated protons or -particles and nuclei from the ambient solar atmosphere. We consider a simple model for the ambient solar atmosphere and beams of accelerated protons or -particles with power-law energy distribution and different angular distributions. The emission spectrum of gyrosynchrotron/synchrotron radiation is obtained by summing the contributions to the total flux density from the secondary electrons and positrons, calculated using a code based on Ramaty’s algorithm from the respective distributions of energy obtained with FLUKA.